A positive association between food insecurity and the prevalence of overactive bladder in U.S. adults - Xiao, Yunfei; Yin, Shan; Bai, Yunjin; Wang, Jiahao; Cui, Jianwei; Yang, Yaqing; Wang, Jia (Frontiers in Nutrition, 2024)
Objective: This study aims to examine the correlation between overactive bladder (OAB) and food insecurity.To explore the association between food insecurity and the prevalence of overactive bladder (OAB).We conducted aA cross-sectional analysis utilizing extensivethe large population data derived from the National Health and Nutrition Examination Survey 2007-2018 was conducted. The status of Household food insecurity is evaluated by the US Food Security Survey Module. Three multivariable logistic regression models were performed tTo elucidateexplore the associationrelationship between food insecurity and the prevalence of OAB, three multivariable logistic regression models were carried out. Additionally, interaction and stratified analyses were also performed to find whether some factors have the potential to alter the correlationcan modify the association.Results: There were 29,129 participants enrolled in the study. Compared to the other three groups, individuals with full food security exhibited a lower proportion of nocturia, urinary urgency incontinence, and OAB. In the fully-adjusted model, it was found that pPeople experiencing food insecurity have a significantly higher prevalence of OAB compared to the those with food security in the fully-adjusted model (OR=1.540, 95%CI 1.359 to1.745). Additionally, there wasA a significant association between the levels of food insecurity and an increased risk of OAB prevalence was also observed (marginal food security: OR=1.312, low food security: OR=1.559, and very low food security: OR=1.759). No significant interaction was seen in the fully-adjusted model.3 Conclusion: There is a strong positive correlation between food insecurity and the prevalence of OAB. Similarly, the correlation between levels of food insecurity and OAB also indicates the same trend.There is a significantly positive association between food insecurity and the prevalence of OAB, and the same trend was also observed in the correlation between the levels of food insecurity and OAB. Namely, the more insecure food, the higher risk of OAB prevalence in the population.